Lung parenchymal trauma biomechanics, mechanisms, and classification: a narrative review of the current knowledge - Koutsouroumpa, Chrysa; Leivaditis, Vasileios; Mulita, Francesk; Papatriantafyllou, Athanasios; Grapatsas, Konstantinos; Baltagianni, Marianthi; Beltsios, Eleftherios; Liolis, Elias; Tasios, Konstantinos; Antzoulas, Andreas; Litsas, Dimitrios; Nikolakopoulos, Konstantinos; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2025)
Lung parenchymal injuries frequently result from thoracic trauma and can lead to significant morbidity and mortality. The lung’s unique biomechanical properties – including its architecture, histology, extracellular matrix (ECM), and respiratory physiology – play a critical role in determining how it responds to mechanical forces during trauma. Based on the mechanism of injury, lung trauma is typically categorized into three primary types: blunt, penetrating, and blast injuries. Each mechanism leads to distinct parenchymal injuries, including contusions, lacerations, herniation, and vascular injuries, which present with unique clinical features and management requirements. A comprehensive understanding of the biomechanics and tissue response to these injuries is essential for optimizing therapeutic strategies and improving patient outcomes in both the acute and long-term phases of lung trauma management. This review aims to provide a detailed exploration of lung parenchymal trauma, focusing on injury mechanisms, classifications, and the importance of accurate diagnosis and treatment.